Factors associated with violence against adolescents at home in Peru - Renzo Rivera; Walter Arias-Gallegos (Interacciones)
Background: Adolescence responds to a period of maturity and adjustment to the adult world; therefore, it is influenced by the social and family context, as well as by the previous stages of development. The objective of the present investigation was to determine the factors associated with violence against adolescents at home in Peru. Methods. A secondary analysis of the National Survey of Social Relations 2015 was carried out. The sample was of 1491 adolescents between 12 to 17 years old. Raw (PR) and adjusted (PRa) prevalence ratios using Poisson regression with robust variance were estimated. Results. It was found that adolescent women (PRa: 1.4; 95% CI: 1.17-1.68) and adolescents who live in homes where there are continuous fights or arguments between parents or adults who live there (PRa: 2.75; 95% CI: 2.11-3.57) have a higher risk of violence. Conclusions. Women and adolescents who live in families where there are continuous arguments between parents or adults have high risk of domestic violence.